Investigative analysis of Hongshan culture pattern design proposed through creative product design - Lin, Lin; Ibrahim, Nur Hisham Bin; Salim, Neesa Ameera Binti Mohamed (International Journal of Asian Social Science, 2024)
Throughout the long history of China, the Hongshan culture stands out as an outstanding and distinctive traditional culture. As a treasure of Chinese art, how to effectively inherit and promote Hongshan culture pottery is a topic worthy of our study. This research purpose to delve into the most representative and unique design features of Hongshan culture, the requirements and ideas of different groups for the application of Hongshan culture pottery patterns in cultural creative products, and explore how to ingeniously integrate these features into the design of cultural creative products. On methodology, using the method of questionnaire survey to analyze the feasibility of applying Hongshan culture pottery pattern elements in cultural creative products, detailed questionnaires are formulated and distributed to respondents via the internet, aiming to obtain extensive participation and diverse perspectives. On findings, data analysis using SPSS software is conducted to reveal common design preferences, resonances, and potential innovative directions among respondents, providing practical and feasible suggestions for the field of creative product design.The practical implications of this study is not only enriches the cultural resources of the current cultural creative market but also helps to promote the dissemination of traditional culture, injecting new vitality into Hongshan culture pottery, and presenting it anew to the public.